The impact of administrative control on the performance of employees: An applied study on the Islamic insurance company - Sorkaty, Mutaz Mohamed; Mokhtar, Ayman Saed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to find out the impact of administrative control on the performance of workers in insurance companies, the modern means and methods used in the implementation of administrative control, and to identify the extent to which the elements of administrative control are available in insurance companies in Sudan. - By application to the Islamic insurance company. The study’s main problem was represented in revealing the extent to which the elements of administrative control are available in insurance companies in Sudan, and their impact on the performance of employees, which leads to achieving the objectives of these service organizations through the research tools used. in the fact that it is one of the studies that examined the reality of administrative control in insurance companies in Sudan and its relationship to the performance of employees, an attempt to address a vital administrative issue that affects the lives of companies and organizations. the study relied on the descriptive-analytical approach in conducting it, through the available sources in the secondary sources and the questionnaire addressed to employees, an intentional sample was taken of the heads of departments, Department managers, assistant general managers and deputy general managers of the Islamic insurance company, numbering 102 people, (93) questionnaires were distributed to the study population, and (90) sound questionnaires were retrieved and used in the analysis with a recovery rate of (96.7%), and the questionnaire was analyzed in the program Statistical SPSS. The study reached several results, the most important of which are: the existence of a statistically significant relationship between the availability of the elements of administrative control and the performance of employees, and it showed that the diversity of control methods used affects positively the development of the performance of employees, and the study showed that there is a slowdown in diagnosing administrative problems and that traditional methods are still used In evaluating the performance of employees. Finally, the study recommended the necessity of updating and continuous development of the organizational structures, the control systems used, and work on diagnosing problems quickly and effectively to follow up on defects and deficiencies.